Neo-realist Avant garde Cinema : Love in the City, Zavattini’s Film Essay - Borjan, Etami (2009)
The aim of the paper is to discuss several topics related to Zavattini’ s idea of cinema that differs in many aspects from the generally accepted neorealist approach. Through the analysis of an episode in the film Love in the City, La storia di Caterina, co-directed by Zavattini and Francesco Maselli, the most prominent issues of Zavattini’ s poetics will be discussed. Film-pedinamento, film lampo, film inchiesta are some of the terms used by Zavattini to describe the new cinema that was supposed to be relatively autonomous to both the official culture and the neorealist cinema. Although credited as “ father of neorealism” Zavattini refused to consider himself the main representative of the movement. He was known as the most famous screenwriter of the period but he never adhered to the official neorealist poetics that was practiced by the most famous neorealist directors such as Rosellini, De Sica and Visconti. He criticized most of the neorealist films and his ideas were more oriented towards the experimental cinema. He was clearly and emphatically dissatisfied with narrative tradition, and expressed his hostility towards dramatic fiction of any kind. Throughout his career of screenwriter, journalist and film critic, Zavattini played a pivotal in the critical rethinking of the new postwar Italian cinema.
Projekt MZOS
ENG